A philosophical clarification of the axiological assumptions behind the concept of goodness in Genesis 1 - Gericke, Jaco (Journal for semitics, 2013)
This paper offers a philosophical clarification of the sense and logic behind the concept of goodness as it occurs in Genesis 1. Many readings of the chapter either bracket these issues or assign it what is thought to be an obvious utilitarian, moral, legal, aesthetic, or theological connotation. The contention of this article is that these views fail to take seriously the metaphysical riddles inherent in the narrative's ontology and beg the question as to the sensibility and folk-philosophical context of the concept of goodness in Genesis 1. Following an initial overview of the relevant data and an outline of the problematic, G.E. Moore's open question argument suggesting the indefinable nature of goodness as a non-natural property is brought to bear on the discussion. The presentation concludes with a philosophical clarification of the axiological assumptions in the text via categories in value theory.